The Effect of Variations in Fly Ash and Metakaolin Binders on The Compressive Strength of Geopolymer Mortar : Pengaruh Variasi Binder Fly Ash dan Metakaolin Terhadap Kuat Tekan Mortar Geopolimer - Aufa Fitria; Tira Roesdiana (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2026)
The purpose of this study wa to examine the effect of varying the binder ratio between fly ash and metakaolin on the compressive strength of geopolymer mortar, as well as to determine the optimum binder mixture composition that would yield the highest compressive strength at room temperature curing. Thi study uses a quantitative approach with laboratory experiments, using variations in the fly ash : metakolin binder ratio, namely 100% : 0%, 70% : 30%, 50% : 50%, 30% : 70% and 0% : 100%, as well as 8 M NaOH and Na2SiO3 activator solutions using a sand : binder ratio of 2,5 : 1. Sixty 5×5×5 cm2 cube shaped test specimens were then tested for compressive strength. This study proves that the combination of fly ash and metakaolin increases the strength of geopolymer mortar. The mixture of 70% fly ash : 30% metakaolin produced the most optimal compressive strength at 28 days, indicating that the reactivity of metakaolin and the aluminosilicate content in fly ash can enhance the geopolymerization prosess and make the microstructure of the mortar more compact. This study proves combining fly ash and metakaolin be more environmentally friendly alternative to portland cement while maintaining its mechanical strength.